SOME RESULTS ON MODEL OF REHABILITATION AND MANAGEMENT OF MULTI - SPECIES MANGROVES AT THUY TRIEU LAGOON, KHANH HOA PROVINCE - Thuy, Nguyen Thi Thanh; Thuy, Nguyen Nhat Nhu; Hieu, Nguyen Trung; Hoa, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2016)
Model of rehabilitation and management of multi-species mangroves has been deployed at both aquaculture area and tidal flat of Thuy Trieu lagoon into which the waste sources from the inland discharged directly. Mangrove propagules including Rhizophora apiculata, R. mucronata and Bruguiera gymnorrhiza were collected at the lagoon and planted directly (10,000 propagules/ha) at both areas. Seeds of Avicennia alba and A. marina, which were also picked at the lagoon, were cultivated into 1 year seedlings before being planted at the tidal flat (6,700 seedlings/ha). With techniques used and co-management mechanism based on the community, determinants for successfulness of the model were confirmed, especially multi-species planting and voluntary direct participation of the shrimp farmers and the Khanh Hoa Sugar factory in the whole stages from site selection to care and management of the restored mangrove areas. After 20 months of planting, the population of the multi-species of mangroves grew well at both areas, in which R. apiculata had a height of 91.47 cm and survival rate of 80.33% in the aquaculture area; a height of 121.44 cm and survival rate of 88% in the tidal flat. After 7 months of planting at the tidal flat, A. alba had a height of 77.69 cm and survival rate of 96%.